GEOGRAPHIC TEACHER'S PERCEPTION ON LEARNING METHODS PROBLEM BASED LEARNING AT SMA NEGERI 13 PANGKEP ACCORDING TO THE SYNTHETIC OF THE 2013 CURRICULUM - Rahmi Kamiruddin; Nasiah Badwi; Ibrahim Abbas (Universitas Negeri Makassar, 2021)
This study discusses the location of the Lae-lae Island tourist attraction, Ujung Pandang District, Makassar City. The purposes of this study are 1) to determine the characteristics of the island of Lae-lae in Makassar. 2) find out the natural tourist attraction of Lae-lae island, Makassar city. 3) See the natural attractions of Lae-lae island, Makassar city. The research used is a type of quantitative research with a descriptive approach. The data analysis technique used is a scoring technique to assign a value to each characteristic parameter of the sub-variables so that the value can be calculated and the ranking can be determined according to the weight of each ODTWA assessment of each criterion multiplied by the weight value of each -respective criteria. the value of the weight/class that has been obtained from the tabulation of the development classification of each assessment criteria, the value of each criterion is averaged to the final score. Through these values will be obtained one of the right locations. The results of the feasible objects and natural tourist attractions of Lae-lae Island are with a value of 78.66%, meaning that Lae-lae Island is included in the category to be developed. Suggestions to the management, community and visitors to continue to maintain the beauty of Lae-lae island and not to do things that are considered to damage the beauty of Lae-lae island.